Do social support and social network influence dental caries in 12-14-year-old schoolchildren of Hyderabad City? - A cross-sectional study - Vishnu Priya Sadhu; M D Shakeel Anjum; V Divya; Vinila Tenali; T Sravya; M Jyothi (Wolters Kluwer Medknow Publications, 2020)
Background: Evidence on the influence of psychosocial factors (social support and social network) on dental caries is scarce in the Indian literature. This assessment is even more important in children, owing to the serious complications of caries that could make their daily activities painful. Aim: We aimed to study if social support and social network influence dental caries among 12-14-year-old schoolchildren of Hyderabad city. Methodology: A cross-sectional questionnaire study was conducted on a sample of 1015 students, and information about social support (using the Multidimensional Scale of Perceived Social Support) and social network (2 questions on number of friends and family members) was recorded. Caries was assessed through the "WHO Dentition Status and Treatment Needs 1997 pro forma" and Decayed, Missed, and Filled Teeth (DMFT) (caries experience) was calculated. Correlation between psychosocial and outcome (D and DMFT) variables followed by binary logistic regression with D and DMFT as the outcome variables in two models were conducted using SPSS 24 with a significance level set at P < 0.05. Results: The mean social support score was 4.10. Almost half of them had a good network of friends and family members. A significant negative correlation was found between "social network family" and both the outcome variables. None of the psychosocial variables predicted caries in the regression. Conclusion: Although psychosocial variables could not predict caries, teaching children about their importance in life and influence on oral health would not only minimize caries but make them healthy and happy.